Supra‐Amphiphiles for Functional Assemblies. (4th September 2016) - Kang, Yuetong; Tang, Xiaoyan; Cai, Zhengguo; Zhang, Xi
Abstract : Supra‐amphiphiles refer to amphiphiles which are fabricated on the basis of various noncovalent interactions and dynamic covalent bonds, including host‐guest interaction, charge‐transfer interaction, electrostatic interaction, imine bonds, etc. In this feature article, recent progresses of supra‐amphiphiles from molecular architecture to functional assemblies will be summarized. A few topics will be specially addressed, including where supra‐amphipihles functions as surfactants, and also in the areas of chemical analysis, nanocarriers, photodynamic therapy, surface modification and catalysis. Abstract : Supra‐amphipihles usually demonstrate responsiveness, reversibility and adaptivity, which are endowed by the dynamic nature of the noncovalent interactions . These properties are desirable for the corresponding applications in various areas, such as nanocarriers, photodynamic therapy, chemical analysis and surface modification. In this Feature Article, the recent progresses of the functional supra‐amphiphiles are demonstrated.